Evaluating the musician with dystonia of the upper limb: a practical approach with video demonstration. Issue 1 (December 2015) - Frucht, Steven
Abstract Focal task-specific dystonia is an unusual movement disorder that may affect musicians specifically when they perform on their instruments. Muscles of the lower face, lower limb and upper limb may be involved depending on the nature of the instrument. We illustrate the rich phenomenology of focal task-specific dystonia affecting the upper limb in musicians, and present a practical approach for evaluating patients in the office.